Innovation of Zakat Literacy Program to Optimize Zakat Funds at BAZNAS Province and BAZNAS Central Lombok Regency Indonesia - Ahyar; Lalu Ahmad Zaenuri; Ulya Hilalatul Hasbi (TASAMUH, 2024)
This study aims to reveal the innovation of the zakat literacy program to optimize the zakat fund in BAZNAS of Central Lombok Province and BAZNAS of Central Lombok Regency, NTB. The research findings show that the innovation of the zakat literacy program by building an online service system (Qris, zakat calculator, digital Zakat, digital ink, and digital urban), restructuring the service system and institutionalizing UPZ-UPZ at the village level. As for the challenges in developing the infrastructure of an online-based service system, the public perception still views Baznas as a zakat collection institution. In contrast, the solution, the two Baznas institutions have strengthened the online service system, partnership networks, and UPZ-UPZ Villages through the Friday Movement program Sedekah Seribu, environment-based zakat zoning mapping, environment-based zakat collection teams, and forming village-level amil.